다중이용시설에서 RadonEye와 RS9A로 측정된 실내 라돈 농도 상관관계 연구 - 유상현; 박종일; 변영태 (한국냄새환경학회, 2020)
Radon is known to be one of the representative carcinogen materials, and may cause severe health damage to the human body with long-term exposure. Without proper treatment such as natural and mechanical ventilation, indoor radon concentration tends to increase as time passes. In this aspect, it is necessary to maintain indoor radon concentration below the domestic indoor air quality (IAQ) management standard by continuous monitoring. However, the number of practical devices which can detect radon concentration is scarce and most of the existing devices are very costly. Among such devices, the RS9A, a prototype of a radon detector, detects indoor radon concentration and is priced significantly lower compared to other existing radon detectors. In this paper, we investigated the RS9A for the continuous detection of indoor radon gas and compared its performance to a commercially available radon detector (RadonEye). We measured indoor radon concentrations at two separate sites by using both detectors simultaneously. The indoor radon concentrations measured by the aforementioned detectors revealed a high correlation. Therefore, the RS9A can be considered as an appropriate candidate for use as a continuous indoor radon monitoring system.